Young Children's Ability to Produce Valid and Relevant Counter‐Arguments. Issue 3 (15th November 2019) - Köymen, Bahar; O'Madagain, Cathal; Domberg, Andreas; Tomasello, Michael
Abstract : In collaborative problem solving, children produce and evaluate arguments for proposals. We investigated whether 3‐ and 5‐year‐olds ( N = 192) can produce and evaluate arguments against those arguments (i.e., counter‐arguments). In Study 1, each child within a peer dyad was privately given a reason to prefer one over another solution to a task. One child, however, was given further information that would refute the reasoning of their partner. Five‐year‐olds, but not 3‐year‐olds, identified and produced valid and relevant counter‐arguments. In Study 2, 3‐year‐olds were given discourse training (discourse that contrasted valid and invalid counter‐arguments) and then given the same problem‐solving tasks. After training, 3‐year‐olds could also identify and produce valid and relevant counter‐arguments. Thus, participating in discourse about reasons facilitates children's counter‐argumentation.